The future of ancient DNA: Technical advances and conceptual shifts. (21st November 2014) - Hofreiter, Michael; Paijmans, Johanna L. A.; Goodchild, Helen; Speller, Camilla F.; Barlow, Axel; Fortes, Gloria G.; Thomas, Jessica A.; Ludwig, Arne; Collins, Matthew J.
Abstract Technological innovations such as next generation sequencing and DNA hybridisation enrichment have resulted in multi‐fold increases in both the quantity of ancient DNA sequence data and the time depth for DNA retrieval. To date, over 30 ancient genomes have been sequenced, moving from 0.7× coverage (mammoth) in 2008 to more than 50× coverage (Neanderthal) in 2014. Studies of rapid evolutionary changes, such as the evolution and spread of pathogens and the genetic responses of hosts, or the genetics of domestication and climatic adaptation, are developing swiftly and the importance of palaeogenomics for investigating evolutionary processes during the last million years is likely to increase considerably. However, these new datasets require new methods of data processing and analysis, as well as conceptual changes in interpreting the results. In this review we highlight important areas of future technical and conceptual progress and discuss research topics in the rapidly growing field of palaeogenomics.